SUV variability in EARL-accredited conventional and digital PET - Koopman, Daniëlle (EJNMMI Res, 2019)
BACKGROUND: A high SUV-reproducibility is crucial when different PET scanners are in use. We evaluated the SUV variability in whole-body FDG-PET scans of patients with suspected or proven cancer using an EARL-accredited conventional and digital PET scanner. In a head-to-head comparison we studied images of 50 patients acquired on a conventional scanner (cPET, Ingenuity TF PET/CT, Philips) and compared them with images acquired on a digital scanner (dPET, Vereos PET/CT, Philips). The PET scanning order was randomised and EARL-compatible reconstructions were applied. We measured SUV(mean), SUV(peak), SUV(max) and lesion diameter in up to 5 FDG-positive lesions per patient. The relative difference ΔSUV between cPET and dPET was calculated for each SUV-parameter. Furthermore, we calculated repeatability coefficients, reflecting the 95% confidence interval of ΔSUV. RESULTS: We included 128 lesions with an average size of 19 ± 14 mm. Average ΔSUVs were 6-8% with dPET values being higher for all three SUV-parameters (p < 0.001). ΔSUV(max) was significantly higher than ΔSUV(mean) (8% vs. 6%, p = 0.002) and than ΔSUV(peak) (8% vs. 7%, p = 0.03). Repeatability coefficients across individual lesions were 27% (ΔSUV(mean) and ΔSUV(peak)) and 33% (ΔSUV(max)) (p < 0.001). CONCLUSIONS: With EARL-accredited conventional and digital PET, we found a limited SUV variability with average differences up to 8%. Furthermore, only a limited number of lesions showed a SUV difference of more than 30%. These findings indicate that EARL standardisation works. TRIAL REGISTRATION: This prospective study was registered on the 31th of October 2017 at ClinicalTrials.cov. URL: https://clinicaltrials.gov/ct2/show/NCT03457506?id=03457506&rank=1.